Verdens Undergang (1916) and the Birth of Apocalyptic Film: Antecedents and Causative Forces - Hamonic, Wynn Gerald (The journal of religion and film, 2016)
This essay describes the antecedents and causative forces giving rise to the birth of apocalyptic cinema in the early 20th Century and the first apocalyptic feature, Verdens Undergang (1916). Apocalyptic cinema's roots can be traced back to apocalyptic literary tradition beginning 200 BCE, New Testament apocalyptic writings, the rise of premillenialism in the mid-19th Century, 19th century apocalyptic fiction, a growing distrust in human self-determination, escalating wars and tragedies from 1880 to 1912 reaching a larger audience through a burgeoning press, horrors and disillusionment caused by the First World War, a growing belief in a dystopian future, and changes in the film industry.